Sexual Harassment of Women Clerical Workers in The Workplace - Abdul Rahim, Rohani (2005)
The issues on sexual harassment caught the national interest in the year 1999. The media frequently highlighted them particularly those happened at workplace. Women became the targeted victims in male dominated workplace and in sexual harassment tolerance environment. Many of those experiences went unreported and they suffered in silence for fear of retaliation and humiliation. In the Iegal perspective, it is essential that the meaning of sexual harassment be determined beforehand. The study is guided by the following research questions: (1) What is the meaning of sexual harassment as perceived by the victims? (2) What is the level of awareness among the victims on sexual harassment? (3) How are the victims harassed and what are the types of sexual harassment experienced? (4) What are the causes of sexual harassment and how do these causes facilitate sexual harassment? (5) How are the victims affected by the sexual harassment experienced? and, (6) How do the victims cope with sexual harassment and why do they choose such means? It uses a qualitative case study approach on ten respondents. They were selected using the purposive sampling and the snowball technique. They were chosen based on criteria, that are: (a) female clerical workers (b) had experienced sexual harassment (c) the sexual harassment occurred at workplace (d) they were employed earlier either in the private or corporate body, and (e) they were more than 20 years old. The respondents were interviewed to draw data based on their experiences. The findings of this study revealed that the victims perceived sexual harassment as unwanted behavior, sexual and sensitive in nature and gender related. There were two levels of awareness found, that are the previous and the recent awareness. The three types of sexual harassment identified by the victims were verbal request, verbal comments and non-verbal display. The causes of sexual harassments were viewed as the existence of opportunities, sexual tolerance environment, the harassers attitude and the victims personality, power and gender relations, and preplanned intention. Some of the effects mentioned by the victims were psychological consequences, changes in personality,..health and social related problems and unsatisfactory work life. Finally, the study found that the victims used some coping strategies to deal with sexual harassments they experienced. That are, social support, self-coping, conduct informal complaint and psychological coping. The conc1usions of the study are as follows: Firstly, there is difficulty in identifying the meaning of sexual harassment. Secondly, there are two levels of awareness about sexual harassment among clerical workers that is, previous and present awareness. Thirdly, the victims were sensitive to sexual harassments that were explicit and sexual in nature. Fourthly, 'opportunities' are regarded as the catalysts that cause sexual harassment among clerical women. Fifthly, emotional psychological and work related factors are most affected by sexual harassment victims and finally, there are problems coping with sexual harassment. The study provides some significant implications. The victims became empowered and their knowledge on sexual harassment was enhanced, after going through the interview sessions that eventually generated awareness on their sexual harassment experiences. In the legal field, data from the study established similar meanings to the "reasonable women standard" used to decide cases in court. This is rather unique and creative because the court uses the layperson standard to decide on the meanings of "sexual harassment". In the organization, greater liabilities were imposed on the employers to ensure the workplaces are free from sexual harassment practices. Future research on every aspect of sexual harassment practices can be conducted in various fields such as social, legal and educational studies. This is because at present there are very limited studies conducted on sexual harassment at workplace in Malaysia.